Results from a multicentre evaluation of plug use for left ventricular assist device explantation - Potapov, Evgenij V.; Politis, Nikolaos; Karck, Matthias; Weyand, Michael; Tandler, René; Walther, Thomas; Emrich, Fabian Christoph; Reichenspurrner, Hermann; Bernhardt, Alexander; Barten, Markus Johannes; Svenarud, Peter; Gummert, Jan; et al. (Interactive cardiovascular and thoracic surgery, 2022)
Myocardial recovery allows for left ventricular assist device (LVAD) explantations after long-term support. Several surgical approaches, including interventional decommissioning, off-pump explantation using a custom-made plug and complete LVAD removal through redo sternotomy, have been described. We present the results from an evaluation of the long-term follow-up of patients who received a titanium sintered plug after LVAD explantation. We performed a retrospective, European, multicentre analysis of patients who received a titanium sintered plug to seal the apical fixation ring after LVAD explantation. Data were collected from a questionnaire that included demographics, procedural details and follow-up information.Out of 54 contacted centres in 12 countries (n = 179 patients), a total of 68 patients were successfully included in the study. The median follow-up was 34 months (interquartile range: 17-58.5 months); 57 (84%) patients had >1-year follow-up. At the time of the last follow-up, 55 (81%) patients were alive, with a Kaplan-Meier 1-year survival of 90.1% (95% confidence interval: 84.0-98.1%) and a 5-year survival of 80.0% (95% confidence interval: 68.4-92.9%). One patient (1.5%) developed a plug infection originating from an infected part of the incorporated driveline and, after complete removal, is currently in good condition. No postoperative stroke has been reported after plug implantation.In this European multicentre study, the use of a custom-made titanium plug to close the apical fixation ring after LVAD explantation resulted in a low incidence of plug-related complications. With the volume of patients undergoing LVAD explantations after myocardial recovery increasing, the plug has evolved as a simple alternative to more invasive device explantation procedures or decommissioning with a high risk for infection of the remaining system or stroke.